2013
DOI: 10.5977/jkasne.2013.19.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Korean Studies on Simulation within Nursing Education

Abstract: The relationship among learning satisfaction, learning attitude, self-efficacy and the nursing student`s academic achievement after simulation-based education on emergency nursing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 28 publications
1
18
0
15
Order By: Relevance
“…Until now, many simulation studies confirmed the self-efficacy of the students and but self-efficacy did not have an adequate effect size [2]. Only two studies confirmed team efficacy [3]. One study [6] found that team efficacy increased after simulation education and another study [29] said that it was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, many simulation studies confirmed the self-efficacy of the students and but self-efficacy did not have an adequate effect size [2]. Only two studies confirmed team efficacy [3]. One study [6] found that team efficacy increased after simulation education and another study [29] said that it was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, SBE using high-fidelity simulators or standardized patients (SP) has been widely used in nursing education. Over the past decade, many studies have been conducted on the effectiveness of SBE in domestic nursing and SBE has been associated with positive learning outcomes in areas of psychomotor, cognition, and affection among students [2,3]. There is a difference in effect size among the three areas and the psychomotor area is the largest and the affective area is the smallest [2] Also, when it comes to measurement variables for each area, clinical performance ability is commonly used in the psychomotor area, knowledge and problem solving ability in the cognition area, satisfaction and selfefficacy in the affection area [2,3].…”
Section: Introduction 1 Backgroundmentioning
confidence: 99%
“…Most of the research was done on new nurses. In addition, there is a lack of research on professional nurses and career nurses who require clinical reasoning ability (Kim, Park, & Shin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research was done on new nurses. In addition, there is a lack of research on professional nurses and career nurses who require clinical reasoning ability (Kim, Park, & Shin, 2013). Benner (1984) proposed five levels of practice for nursing (novice, advanced beginner, competent, proficient, and expert).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with simulation training, the students can experience academic achievement and improvement, as well as critical thinking in clinical performance, enhanced confidence and satisfaction, the by using scenarios similar to actual situations, they can learn about the way of improving the communication skills between the patients plus care givers and the health professionals, the patient safety, the interdisciplinary cooperation among the various medical teams and acquire the ability to manage difficult situations [15][16].…”
Section: Introductionmentioning
confidence: 99%